1987
DOI: 10.1007/bf01721038
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hyperprolactinemia and plasma lipids in women

Abstract: Plasma total cholesterol (TC), triglycerides (TG), high-density lipoprotein-cholesterol (HDL-C), and low-density lipoprotein-cholesterol (LDL-C) were studied in 15 hyperprolactinemic women who had a prolactin (PRL) adenoma, in comparison to 15 age-matched control women. In the hyperprolactinemic group, plasma lipids were also correlated to age, excess body weight (EBW), plasma PRL, and estradiol-17 beta (E2). Plasma TC, TG, and LDL-C were similar in both hyperprolactinemic and control women, while plasma HDL-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…Bonithon-Kopp et al (20) suggested a mean carotid IMT > 0.75 mm as a measure of subclinical atherosclerosis. In our study 16.67% of PCOS cases met the criteria against none in the control group. 10% of PCOS women approached (0.7 mm) this value.…”
Section: Among Clinically Diagnosed Pcosmentioning
confidence: 47%
See 1 more Smart Citation
“…Bonithon-Kopp et al (20) suggested a mean carotid IMT > 0.75 mm as a measure of subclinical atherosclerosis. In our study 16.67% of PCOS cases met the criteria against none in the control group. 10% of PCOS women approached (0.7 mm) this value.…”
Section: Among Clinically Diagnosed Pcosmentioning
confidence: 47%
“…We estimated serum TSH and Prolactin levels to rule out hypothyroidism and hyperprolactinemia as possible causes of dyslipidemia (15,16) cases. However as data of Table 2 shows, both of these hormones were within normal limits (TSH: 0.4 -6μIU/ml and Prolactin: 3 -23 ng/ml) and were not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, decreased HDL and increased CHOL and TG have been reported in patients with prolactinomas as compared to controls [75,76,77,78], and a direct correlation between lipid metabolism and PRL levels has been proposed [48]. PRL can directly act on adipose tissue and may be involved in the lipid metabolism of mature adipocytes [79,80,81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperprolactinemia leads to a reduction in estrogen levels by inhibiting the gonadotropin releasing hormone secretion, which may lead to an elevation in total and LDL-C and decrease in HDL-C [7]. Total C/ HDL C ratio, which has been approved as a new atherosclerotic risk marker for endothelial dysfunction in AACE 2012 Lipid and Atherosclerosis guidelines [20], were similar between three groups.…”
Section: Discussionmentioning
confidence: 86%
“…Ling et al demonstrated that, PRL increase triglyceride (TG) levels by reducing the lipoprotein lipase activity in adipose tissue [6]. Hyperprolactinaemia is associated with amenorrhoea and decreased estrogen concentration which may lead to the elevation in total cholesterol and low density lipoprotein cholesterol (LDL-C) and decrease in high density lipoprotein cholesterol (HDL-C) [7]. The aim of present study was to evaluate the metabolic parameters in non obese patients with prolactinoma and effect of cabergolin treatment on this parameters.…”
Section: Introductionmentioning
confidence: 99%